Validated model transformation-driven software development. (28th March 2008) - Lengyel, Laszlo; Levendovszky, Tihamer; Charaf, Hassan
Model-driven Software Engineering is one of the most focused research fields. Model processors automatically generate the lower level artefacts. Graph transformation is a widely used technique for model transformations. Especially visual model transformations can be expressed by graph transformations. This paper presents a visual control flow support of the Visual Modelling and Transformation System and discusses the principles of the constraint-driven validated model transformation. The presented approach helps to validate, preserve or guarantee certain model properties not only for individual transformation rules but also for the whole transformation.